Repeated semen exposure decreases cervicovaginal SIVmac251 infection in rhesus macaques - Shaheed A. Abdulhaqq (Nature Portfolio, 2019)
High frequency semen exposure has been associated with activation of anti-HIV mechanisms in HIV negative sex workers. Here, Abdulhaqq et al. show that repeated vaginal exposure to semen reduces vaginal infection by SIV in non-human primates, and is associated with lower CCR5 expression in CD4 T-cells and a local type-I interferon response.